2011
DOI: 10.1111/j.1741-2358.2011.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of therapeutic effect of aqueous extract of garlic and nystatin mouthwash in denture stomatitis

Abstract: Comparison of therapeutic effect of aqueous extract of garlic and nystatin mouthwash in denture stomatitis Introduction: Denture stomatitis (DS) is the most common form of chronic oral candidiasis. The standard treatment for DS is nystatin, which is accompanied with complications such as a bitter taste. The aim of this study was to compare the effect of garlic with nystatin in DS. Material and Methods: This randomised clinical trial study was performed on 40 patients with DS. After obtaining written consent, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 15 publications
2
68
0
4
Order By: Relevance
“…Although these agents exhibit therapeutic efficacy, their side effects limit their usage. Some of the most common side effects are bitter taste, localized allergic reactions following application, nausea and vomiting, possible adrenal insufficiency, and hepatic necrosis (9,23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these agents exhibit therapeutic efficacy, their side effects limit their usage. Some of the most common side effects are bitter taste, localized allergic reactions following application, nausea and vomiting, possible adrenal insufficiency, and hepatic necrosis (9,23).…”
Section: Discussionmentioning
confidence: 99%
“…A participant should have type 2 denture stomatitis, should have worn dentures for at least 6 months, and should not have a systemic disease that compromises the immune system such as diabetes. Participants should not have any disorder that causes muscle weakness, such as Parkinson's disease, or that limits cognitive functioning, such as dementia or psychosis (23). Patients should not have a history of use of antifungals, antibiotics, or drugs that reduce saliva production (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time-kill assay revealed that aqueous garlic extract showed better antiproteolytic effects on total Porphyromonas gingivalis protease activity compared with ethanolic garlic extract (Shetty, Thomas, Shetty, Bhandary, & Shetty, 2013 Lavage with lipophilic allicin combined with vancomycin inhibited biofilm formation by S. epidermidis in a rabbit model of prosthetic joint infection (Zhai, Pan, Pang, & Bai, 2014). In a pilot study of patients with denture stomatitis, a mouthwash with garlic aqueous extract was superior to nystatin primarily due to less adverse effects (Bakhshi, Taheri, Shabestari, Tanik, & Pahlevan, 2012). In a clinical pilot study done over a 7-day period, a mouthwash containing garlic extract was superior to the negative control but inferior to 0.2% CHX in reducing salivary S. mutans count, one of the primary etiological organisms known to cause dental caries (Chavan, Shetty, & Kanuri, 2010).…”
Section: Fermented Black Garlicmentioning
confidence: 99%
“…It is also considered that garlic in combination with nystatin may be highly effective in the treatment of oral candidiasis, in particular those associated with denture stomatitis (9,47 …”
Section: Alternative Agents In the Treatment Of Denture Stomatitis Asmentioning
confidence: 99%